Family Structure and History of Childhood Trauma: Associations With Risk-Taking Behavior Among Adolescents in Swaziland - Mokoena Patronella Maepa; Thobile Ntshalintshali (Frontiers Media S.A., 2020)
Introduction: Risk-taking and self-harm behavior among adolescent are a global challenge. This study explored family structure and history of childhood trauma and their association with risk-taking and self-harm behaviors among adolescents in Swaziland.Methods: Using a cross-sectional design, a sample of 470 male and female adolescents were sampled through simple random sampling from selected high schools in Swaziland. They completed a questionnaire assessing family structure, history of childhood trauma, and risk-taking and self-harm behaviors. Analysis of variance and t-test were used to analyze the results.Results: The findings revealed that family structure significantly influence risk-taking and self-harm behavior among adolescents [F(2, 247) = 5.481; P < 0.004] those from child-headed and single-parent households reported higher risk-taking and self-harm behaviors. The results also revealed adolescents history of childhood trauma to be more risk-takers than those without history of childhood trauma t(468) = 3.409, p < 0.001.Discussion: Study results suggest that family structure and history of childhood trauma have significant association with adolescents' risk-taking and self-harm behaviors.